Sistem Irigasi Sawah Berbasis Internet Of Things Memanfaatkan Energi Panas Matahari Dengan Panel Surya - Muhammad Alfiyan; Arief Budi Laksono; Rifky Aisyatul Faroh (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2025)
The rice field irrigation system based on the Internet of Things (IoT), utilizing solar energy through photovoltaic panels, is designed to improve agricultural efficiency, particularly in automating water distribution. This system consists of a soil moisture sensor, water level sensor, 12V DC water pump, servo motor for opening the irrigation gate, and an ESP32 microcontroller connected to the Blynk application to monitor and control irrigation in real-time via smartphone. Electrical energy is supplied by solar panels and stored in batteries through a solar charge controller (SCC), allowing the system to operate independently of the main power grid. Test results show that the system can accurately read soil moisture and water level, activate the pump, and open the irrigation gate according to user commands via the Blynk app. The use of renewable energy and remote control makes this system an innovative solution to support sustainable agriculture and address water scarcity in rice fields, especially during the dry season.